Efektivitas Metode Eksperimen dalam Pembelajaran pada Materi Perubahan Wujud Benda Di SD Negeri 1 Tahunan - Wahyu Widdiya Sari; Erna Zumrotun (Lembaga Bale Literasi, 2025)
This study aims to examine the extent to which the experimental method can improve students' learning outcomes regarding changes in the state of matter in grade V of SD Negeri 1 Tahunan. The method applied is quantitative with One Group Pretest-Posttest Design. The research subjects consisted of grade V students. Data were collected by pretest and posttest and analyzed using paired t-test. The research findings show a significant difference between learning outcomes before and after treatment in grade V. These results indicate that the experimental method in learning can significantly improve students' conceptual understanding, encourage active participation, and train critical and scientific thinking skills. The results of the validity and reliability tests show that the test instrument is valid and reliable. This study indicates that the application of the experimental method is very effective in teaching science at the elementary school level, especially on the topic of changes in the state of matter, and it is recommended to be carried out more widely with innovative planning according to school conditions.